LEO Augmentation in Large-Scale Ionosphere-Float PPP-RTK Positioning - Wang, K.; El-Mowafy, Ahmed; Cheng, F.; Yang, X. (2024)
Precise point positioning-real-time kinematic (PPP-RTK) positioning combines the advantages of PPP and RTK, which enables the integer ambiguity resolution (IAR) without requiring a reference station nearby. The ionospheric corrections are delivered to users to enable fast IAR. For large-scale networks, precise interpolation of ionospheric delays is challenging. The ionospheric delays are often independently estimated by the user, in the so-called ionosphere-float mode. The augmentation of low Earth orbit (LEO) satellites can bridge this shortcoming thanks to their fast speeds and the resulting rapid geometry change. Using 30-s real dual-frequency Global Positioning System (GPS) and Beidou Navigation Satellite System (BDS) observations within a large-scale network of thousands of kilometers, this contribution tests the effects of LEO augmentation using simulated dual-frequency LEO signals from the navigation-oriented LEO constellation, CentiSpace. Results showed that the LEO augmentation makes the solution convergence less sensitive to the original Global Navigation Satellite System (GNSS)-based model strength. The improvements in the convergence times are significant. For example, in the kinematic mode, the convergence time of the 90% lines of the GPS/BDS-combined ambiguity-float horizontal solutions to 0.05 m is shortened from more than 60 to 3.5 min, and that of the GPS-only partial ambiguity resolution (PAR)-enabled horizontal solutions is shortened from more than 20 to 4.5 min. In both the ambiguity-float and PAR-enabled cases, the 68.27% (1σ) lines of both the kinematic and static horizontal and height errors can converge to 0.05 m within 4 min, and for the 90% lines, within 6.5 min in all cases. The 90% line of the GPS/BDS/LEO combined PAR-enabled solutions can converge to 0.05 m within 2.5 and 3 min in the horizontal and up direction, respectively. Results also showed that enlarged projection of the mismodeled biases on the user coordinates were observed in the LEO-augmented scenario after convergence or ambiguity resolution. This is mainly due to the lower orbital height and low elevation angles of the LEO satellites, which requires further research when real LEO navigation signals are available.